KARAKTERISTIK EDIBLE FILM BERBASIS GEL BUAH OKRA (Abelmoschus esculentus L) DENGAN PENAMBAHAN CMC (CARBOXY METHYL CELLULOSE) DAN GLISEROL - Warkoyo Warkoyo; Ardiana Desi Ayu Taufani; Rista Anggriani (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The gel found in okra fruit is a long-chain hydrocolloid polysaccharide which can be used as a stabilizer in edible films. Previous study showed that addition of cmc and glyserol 0.50% : 0.75% in edible film based on okra fruit gel resulted 24.83 MPa of tensile strength and moderate elongation (18.09%). Meanwhile, cmc is used to improve the tensile strength and elongation of edible film and glycerol as a plasticizer. So it need to reformulate between cmc and glycerol by increasing its concentration. The aim of this research is to access the characteristic of edible films based on okra fruit gel due to the increase of cmc and glycerol concentration more than 1%, in order to produce edible films characteristic that meet standards. The results showed that the treatment of cmc 3% and glycerol 1.5% produced edible films that met the standards with 0.17 mm of thickness, 31.62 % of solubility, 1.07 A546/mm of transparency, 19.56 MPa of tensile strength, and 3.31 g/m2/h of WVTR. More over, the elongation in this treatment obtained up to 186%. Thus, the edible film of this treatment has great potential as an alternative to food packaging